2017
DOI: 10.17221/134/2016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent feline gastrointestinal eosinophilic sclerosing fibroplasia and presumptive eosinophilic cystitis in a domestic short-haired cat: a case report

Abstract: This report describes recurrent feline gastrointestinal eosinophilic sclerosing fibroplasia (FGESF) and eosinophilic cystitis in an 8-year-old domestic short-haired cat. The cat presented with incontinence, pollakiuria, vomiting and weight loss. An abdominal mass was palpated and ultrasonography revealed severe segmental thickening of the jejunal wall with loss of layering. Complete resection of the jejunal mass was performed. The resected mass was composed of branching trabeculae of dense collagen, intermixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
(49 reference statements)
0
7
1
Order By: Relevance
“…Up to 58% of patients with FGESF reported in the current literature showed a systemic eosinophilia, suggesting a potential, unusual presentation of feline eosinophilic granuloma complex. 4,7,9,10 However, our case, and cats reported elsewhere, 1,10 did not show systemic eosinophilia, indicating that a lack of systemic eosinophilia does not rule out FGESF. Furthermore, it is unclear whether the development of systemic eosinophilia is a negative prognostic factor for FGESF.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Up to 58% of patients with FGESF reported in the current literature showed a systemic eosinophilia, suggesting a potential, unusual presentation of feline eosinophilic granuloma complex. 4,7,9,10 However, our case, and cats reported elsewhere, 1,10 did not show systemic eosinophilia, indicating that a lack of systemic eosinophilia does not rule out FGESF. Furthermore, it is unclear whether the development of systemic eosinophilia is a negative prognostic factor for FGESF.…”
Section: Discussioncontrasting
confidence: 64%
“…11 Interestingly, elevated CK levels were not seen in previously reported cases. [1][2][3][4][5][6][7][8][9][10][11][12][13] Another important aspect of FGESF is the therapeutic approach. Currently, multimodal therapy combining surgical debulking of the mass (biopsy vs complete surgical resection), symptomatic therapy, antibiotic therapy (especially if intralesional bacteria are found) and immunosuppressive therapy using prednisone or ciclosporin A has been described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilic cystitis has also been reported in dogs with uroliths and secondary non‐neoplastic bladder wall masses 5 . Eosinophilic cystitis has been reported in a single cat with recurrent feline gastrointestinal eosinophilic sclerosing fibroplasia; and whose urine also cultured positive for Mycoplasma 6 . There was no previous history of drug therapy in this animal, and no uroliths, sclerosing fibroplasia, or neoplasms were found in the bladder at post mortem.…”
Section: Discussionmentioning
confidence: 73%
“…2,[13][14][15] A mass in a second location develops in some of the cases, after surgical removal of the initial mass. 16,17 The prognosis varies between studies; however, no large studies on prognosis or response to treatment have been reported. 2 The objective of this study was to retrospectively evaluate a large number of cats with GESF, including their presentation, diagnosis, treatment, and outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical removal of the mass has been performed in most cases; however, several studies report medical management with administration of corticosteroids, cyclosporine, and mycophenolate 2,13‐15 . A mass in a second location develops in some of the cases, after surgical removal of the initial mass 16,17 …”
Section: Introductionmentioning
confidence: 99%